THE DESIGN OF "CATVISOR" SUNSCREEN USAGE REMINDER MOBILE APPLICATION FOR COLLEGE STUDENTS - Verdian, Salsabila Aurielya; Apsari, Diani; Barlian, Yelly Andriani (eProceedings of Art & Design, 2024)
Sunscreen is an important way to protect your skin from the harmful e昀昀ects of UVrays. However, many people o昀琀en forget to apply sunscreen or do not use it properly, pu琀ngthem at risk of sunburn, skin damage and skin cancer. Indonesia is also located on the equatorwhich allows exposure to high-intensity sunlight, so it is very important for people to usesunscreen in their daily lives. Life琀椀me sun exposure is posi琀椀vely associated with skin damageand skin aging, especially in younger people, these indicate that most people's knowledge andbehavior have shown a low level of sunscreen use, including educa琀椀on about the importance ofusing sunscreen needs to be done to improve this condi琀椀on. A poten琀椀al solu琀椀on to this problemis to use media reminders to encourage people to use sunscreen. Therefore, this paper is usedto summarize the process of designing and interac琀椀ve media educa琀椀on by using qualita琀椀ve as the research method and use ques琀椀onnaire, observa琀椀on, interview and literature study as theData Collec琀椀on and SWOT and Matrix as the data analysis to remind people the importance ofusing sunscreen in our lives, and will explain the basis for crea琀椀ng applica琀椀ons as the media thatcan remind people to wear sunscreen and providing knowledge about the UV index, so thatpeople can be琀琀er understand the use of sunscreen and did not forget to use sunscreen everyday. Keywords: design for healthcare, edutaintment, interac琀椀ve design, mobile applica琀椀on,sunscreen reminder user interface